Cost Effectiveness Analysis of Favipiravir and Oseltamivir Antiretroviral Covid-19 Patients in Bogor Cisarua Lung Hospital - Ani Rahayu; Dwi Puspita Sari; Lukluk Utami Ningsih; A. Triwildan ST Fatimah (Biology, Medicine, & Natural Product Chemistry, 2025)
Favipiravir is a type of RNA-dependent RNA polymerase (RdRp) inhibitor. Favipiravir is converted by host enzymes to T-705-ribofuranosyl 5-triphosphate and may act as a nucleotide analogue that selectively inhibits viral RNA-dependent RNA polymerase or causes lethal mutagenesis upon insertion into viral RNA without cytotoxicity in mammalian cells. Oseltamivir is part of the neuraminidase inhibitors (NAIs) group which has a mechanism of action by inhibiting viral neuraminidase. Most of the alternative therapies for Covid-19 require pharmacoeconomic studies, especially regarding cost-effectiveness analysis which is useful in balancing patient expenses by determining treatment alternatives that represent the best health outcomes at a more affordable cost. The aim of this study was to compare the cost effectiveness of the antiretrovirals Favipiravir and Oseltamivir. This research method used a descriptive analytic cross-sectional design and data collection was carried out retrospectively from the medical records of Covid-19 sufferers while detailed data on medical expenses were obtained from the finance department of inpatients at Cisarua Pulmonary Hospital, Bogor for the period September-October 2022. Sample of 80 patients consisted of 40 patients using Favipiravir and 40 patients using Oseltamivir. The parameters used in this research are direct medical costs (which include doctor visit costs, treatment room costs, laboratory costs and drug costs) while the effectiveness uses a negative RT PCR value. The results showed that in patients using Favipiravir with an average length of treatment 6.525 days, the total cost was Rp. 9,930,327/patient and Cost-Effectiveness Ratio (RP/day/patient) Rp. 1,521,899.195, whereas in patients using Oseltamivir with an average length of treatment 7.925 days, the total cost was IDR. 12,368,397/patient and Cost-Effectiveness Ratio (Rp/day/patient) IDR. 1,560,681,009. It can be concluded that Favipiravir is more cost effective than Oseltamivir.